Deontological analysis on Oscar Wilde’s selected fairy tales - Kiang, Chyu Vey (2020)
Classic fairy tale authors often use death for moral lessons due to its association with punishment towards evil characters for their actions. But Oscar Wilde’s fairy tales contradict the typical connotation of deaths, whereby his own characters experienced death or physical disfigurement. Therefore, this study aims to investigate the theme of morality in Wilde’s selected fairy tales based on the deontological approach. This study addressed the relationship between the personalities and actions of Wilde’s main characters, followed by the consequences which comprise death and/or physical disfigurement. In addition, the study will determine the moral permissibility of the characters’ maxims underlying their actions in application of Kantian Ethics. Based on the findings, Kantian theory suggests that the actions of Wilde’s main characters are motivated by their desires that reflect their personalities which comprises their principles and beliefs. The study also addressed the consequences of their actions that contradict the general connotations of death. Besides, the analysis suggests that the maxims underlying the actions of Wilde’s characters could be categorised into “for duty” and “for other means”. Readers would be able to use a deontological approach to understand a character without consideration of the typical “right versus wrong” principle.